2012
DOI: 10.1186/1471-2180-12-9
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-8 is the single most up-regulated gene in whole genome profiling of H. pylori exposed gastric epithelial cells

Abstract: BackgroundThe association between Helicobacter pylori infection and upper gastrointestinal disease is well established. However, only a small fraction of H. pylori carriers develop disease, and there are great geographical differences in disease penetrance. The explanation to this enigma lies in the interaction between the bacterium and the host. H. pylori Outer Membrane Phospholipase A (OMPLA) has been suggested to play a role in the virulence of this bacterium. The aim of this study was to profile the most s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 72 publications
3
63
0
1
Order By: Relevance
“…ASPP2 is often down-regulated in many aggressive malignancies and gastric cancers (35)(36)(37). Infection with Hp and delivery of CagA increases the level of ASPP2 (21,38). Furthermore, after Hp infection, CagA coimmunoprecipitates with ASPP2 and alters its proapoptotic function (21).…”
Section: Significancementioning
confidence: 99%
“…ASPP2 is often down-regulated in many aggressive malignancies and gastric cancers (35)(36)(37). Infection with Hp and delivery of CagA increases the level of ASPP2 (21,38). Furthermore, after Hp infection, CagA coimmunoprecipitates with ASPP2 and alters its proapoptotic function (21).…”
Section: Significancementioning
confidence: 99%
“…IL-8 production is also recognized as an early response to H. pylori by the gastric epithelium (14). A number of H. pylori factors are known to cause gastric inflammation and epithelial damage.…”
Section: Discussionmentioning
confidence: 99%
“…Induction of cytokine secretion by H. pylori depends on both the host genetic background and microbial virulence (9). Among these cytokines, IL-8 is the most highly expressed gene in H. pylori-infected gastric epithelial cells and appears to play a major role in the epithelial cell response to H. pylori infection and in the pathological processes leading to gastric disease (14,15). Several studies have demonstrated increased IL-8 production and secretion in response to H. pylori both in vivo and in vitro (16,17).…”
mentioning
confidence: 99%
“…Accordingly, an H. pylori mutant strain lacking pldA1 is unable to colonize the murine gastric mucosa (77), and strains isolated from patients suffering peptic ulcer display high lysophospholipid content (78). However, pldA1expression does not play a role in enhancing IL-8 production or the acute inflammatory response to H. pylori (79).…”
Section: Acyl Hydrolases: Phospholipases a And Bmentioning
confidence: 99%